Impact of human activities on changes of ichthyofauna in Dongjin River of Korea in the past 30 years. Issue 3 (17th May 2017) - Ko, Myeong-Hun; Kwan, Ye-Seul; Lee, Won-Kyung; Won, Yong-Jin
ABSTRACT: Ichthyofauna and fish community were investigated at 17 representative stations of the Dongjin River drainage system from spring to fall in 2014. The survey resulted in a list of 53 species belonging to 14 families structured into 4 distinctive parts along the river: uppermost-stream, upper-stream, mid-stream, and lower-stream. Comparison of species lists with 30-year interval exhibited significant decreases in peripheral freshwater fishes, Acheilognathinae, endemic, and indigeneity species, but increases in exotic, epipelagic, and lentic species. Moreover, in the estuary of the Dongjin River drainage system, peripheral freshwater fish species were replaced by pure freshwater fish species due to the Saemangeum sea-wall project. In the upper region of the river, introduced eight alien species from Seomjin River via water diversion tunnels. In the mid-lower region, the construction of floodgates and numerous small weirs caused expansion of lentic water areas, facilitating the spread of problematic exotic species such as Micropterus salmoides, Lepomis macrochirus, and Carassius cuvieri . Also, water deterioration in this region resulted in an increase of tolerant species and a decrease of sensitive and endemic species. Our results suggest that a recovery strategy for a healthy ecosystem in the Dongjin River drainage system should reflect this compartmentalized cause and effect on the changes of icthyofauna.